Discussion of an Experiment on Nonsampling Errors - Boutell, Wayne S. (Journal of Accounting Research, 1970)
It is always difficult to replicate actual business conditions in an experimental design, but I would certainly like to see more of the type of research that Professor Sauls has undertaken in connection with his work on nonsampling errors. My comments will be divided into three parts: comments on the design of the sampling plan, specific comments on the conclusions, the problem of formulating general recommendations based on specific experimental results. The population from which Sauls drew his samples is a curious and homogeneous one. In general the population consists of academic and staff employees at Michigan State University. The population is also surprisingly small. There are 478 members in the Michigan State employee credit union. 22 of these members were deleted by Sauls for various reasons, although these reasons are not explicitly stated in the paper; and even in the remaining total of 456 members, there were apparently some members of the same family. This might tend to bias the sample results if they had been selected; namely, the criteria of independence of individual members of the population could not be maintained in all cases. Regarding the sample plan itself, two samples of 50 and two samples of 30 were used; and these represented an apparently arbitrary sample size. I think that some explanation would help the reader evaluate the criteria behind the selection of these particular sample sizes. Given the particular confidence levels of the sample sizes, the interval estimates for acceptance of the null hypothesis are extremely broad. An example will demonstrate the problem in this connection. Six people (21%) in one of the samples confirmed a higher balance than the actual balance while three people (10%) in the same sample confirmed a lower balance than the actual one; but because of the width of the interval estimate, the author accepted the